Epilepsy : global issues for the practicing neurologist - Engel, Jerome, Jr (World Federation of Neurology seminars in clinical neurology, 2005)
This volume is the second in a series developed under the auspices of the World Federation of Neurology to meet the needs of neurologists who must practice medicine without many of the advantages that are often taken for granted in the industrialized world. It is targeted to neurologists practicing in low-resource environments and those who wish to practice cost-effective neurology, and addresses issues important for neurologists in developing countries that are not covered in standard textbooks. The series will update the reader in currently accepted diagnostic and management practice. Materi.